Common symptoms for a rare disease in a girl with sarcoidosis: a case report - Mattia Giovannini; Michele Luzzati; Giovanna Ferrara; Anna Maria Buccoliero; Gabriele Simonini; Maurizio de Martino; Rolando Cimaz; Teresa Giani (BMC, 2018)
Abstract Background Sarcoidosis in pediatric age is uncommon and challenging diagnosis, because manifestations can be significantly variable and non-specific since it is a multisystem disease, and virtually any organ system may be involved. Case presentation In this report, we describe the case of a 12-year-old girl presenting with fatigue and weight loss, with a painless hepato-splenomegaly without additional clinical signs on physical examination. In our patient, once we had ruled out infections, malignancies and granulomatous diseases of childhood, we made diagnosis of sarcoidosis, finding suggestive histological features in two different tissues (liver and lymph nodes) with lung involvement. Conclusions Our case points out that pediatricians should consider sarcoidosis in the differential diagnosis in case of systemic symptoms, even in absence of other specific clinical clues, because they represent the most common clinical manifestations on presentation in children, in order to refer promptly the young patient to specialist evaluation.